The Study of the Ethical and Practical Barriers to Using ChatGPT for Academic Writing - Kuraesin, Cicin; Fauziyyah, Gesha Lailatul; Ruminda, Ruminda; Rohadi, Tedi (Journal of English Education and Teacher Trainer, 2025)
This study investigates the ethical and practical barriers to using ChatGPT for academic writing from students' perspective. This study used a qualitative research design to examine the ethical and practical challenges that university students face when using ChatGPT for academic writing. Fifteen participants were randomly selected from undergraduate and master's programs at ten universities in West and Central Java who used ChatGPT for their academic writing. The result showed ChatGPT’s use in academic writing presents both ethical and practical challenges. Ethical issues include the risk of plagiarism, undermining critical thinking, and maintaining research authenticity, along with concerns about unreliable information and unclear institutional policies. Practical barriers involve limitations like the need for a professional version (ChatGPT-Pro), difficulty in verifying accuracy, formatting issues, lack of depth in analysis, and repetition of content. To ensure responsible use, these barriers require clear institutional guidelines and ethical standards.